Youth capacity building in preventing risky sexual behavior in rural areas - Ema Waliyanti; Dewi Puspita; Alfauzi Adhe Destyanto; Sofia Mutmainnah; Harningsih Putri Mustikasari; Rizal Aji Prabowo (Universitas Muhammadiyah Magelang, 2022)
Teenagers, as the nation's next generation, have the right to optimal growth and development, as well as the assurance of their survival, free of discrimination and mistreatment, and protection from a variety of health concerns. This group has health issues, owing to a proclivity towards risky behavior. Strengthening teenagers' abilities to inhibit sexual behavior in teenagers is the solution to this problem. This activity was carried out in Bangunjiwo Village, Kasihan, Bantul, Yogyakarta. Through video media, lectures, and peer group discussions, this program aims to educate youth about risky sexual behavior. The results of the program indicate that health education using video media, lectures, and peer groups can improve rural teenage knowledge and attitudes about risky sexual behavior. This activity is expected to promote teenager understanding, attitudes, and reduce risky sexual activity, as well as provide a venue for seeking alternate solutions to reproductive health problems.